2022
DOI: 10.4093/dmj.2021.0146
|View full text |Cite
|
Sign up to set email alerts
|

Glial and Vascular Cell Regulation of the Blood-Brain Barrier in Diabetes

Abstract: As a structural barrier, the blood-brain barrier (BBB) is located at the interface between the brain parenchyma and blood, and modulates communication between the brain and blood microenvironment to maintain homeostasis. The BBB is composed of endothelial cells, basement membrane, pericytes, and astrocytic end feet. BBB impairment is a distinguishing and pathogenic factor in diabetic encephalopathy. Diabetes causes leakage of the BBB through downregulation of tight junction proteins, resulting in impaired func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 113 publications
(150 reference statements)
0
8
0
Order By: Relevance
“…As CAA progresses, the neurovascular unit degenerates in amyloid-laden vessels [ 40 , 53 ], affecting the integrity of the vessel wall and resulting in BBB leakage, vessel occlusion or rupture, leading to hemorrhage and decreased cerebral blood flow [ 2 ]. Also, under diabetic conditions, both the capillaries and larger vessels of the brain show a thickened basal lamina from collagen deposition, accumulated byproducts of lipid peroxidation, and deterioration of endothelial cells and pericytes [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As CAA progresses, the neurovascular unit degenerates in amyloid-laden vessels [ 40 , 53 ], affecting the integrity of the vessel wall and resulting in BBB leakage, vessel occlusion or rupture, leading to hemorrhage and decreased cerebral blood flow [ 2 ]. Also, under diabetic conditions, both the capillaries and larger vessels of the brain show a thickened basal lamina from collagen deposition, accumulated byproducts of lipid peroxidation, and deterioration of endothelial cells and pericytes [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, oxidative stress has a key role in insulin resistance and progression of diabetes [ 73 , 74 ] and diabetic mice show vascular alterations associated with increased oxidative stress, pericyte dysfunction and cerebrovascular integrity compromise [ 75 ]. Likewise, advanced glycation end products, resulting from hyperglycemia in T2D, alter the structure and function of BBB proteins [ 62 ] and diabetes-induced inflammation leads to astrocytic feet swelling in small vessels, separation of the plasma membrane and accumulation of hypertrophic microglia [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the intricate and complex association of metabolic disorders with the vascular unit, it is postulated that a diabetic condition is likely to alter the function of cells in the BBB interface integrity ( Li et al, 2022 ). Lee and co-workers found that cellular components can affect the integrity of BBB via the interchange of metabolic byproducts ( Lee et al, 2022 ).…”
Section: Role Of Autophagy In Pericyte Activitymentioning
confidence: 99%
“…In MS, Wnt signaling dysfunction leads to blocked migration of NG2-glia along the vasculature, while NG2-glia accumulate around the vasculature, physically expelling astrocyte endfeet from the vascular surface, disrupting TJPs between endothelial cells, and increasing BBB permeability (Niu et al, 2019). Moreover, the proliferation of NG2-glia further exacerbates BBB injury in a diabetic model (Li et al, 2022a) and NG2-glia secrete matrix metalloproteinase 9 (MMP-9) to disrupt BBB integrity in the early stages of WM injury (Hu et al, 2022).…”
Section: Regulation Of Bbb Permeability By Ng2-gliamentioning
confidence: 99%